2010
DOI: 10.1227/01.neu.0000368102.22612.47
|View full text |Cite
|
Sign up to set email alerts
|

The Transcrusal Approach

Abstract: The transcrusal approach provides adequate exposure for most petroclival lesions and giant aneurysms of the upper basilar artery while offering the possibility of hearing preservation. Like all approaches to large tumors and aneurysms in this region, there is a significant risk of morbidity and mortality. However, this approach is an excellent alternative to other techniques that necessitate deliberate sacrifice of ipsilateral hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With the lesion not conforming to these attributes, the surgeon may need to convert to a transcrusal/ translabyrinthine approach, to skeletonization/posterior displacement of the SS, or to undertake a retrosigmoid approach. 6 10…”
Section: Discussionmentioning
confidence: 99%
“…With the lesion not conforming to these attributes, the surgeon may need to convert to a transcrusal/ translabyrinthine approach, to skeletonization/posterior displacement of the SS, or to undertake a retrosigmoid approach. 6 10…”
Section: Discussionmentioning
confidence: 99%
“…Obliteration of the canals begins away from the ampullated end and proceeds with a leading edge maintaining a seal with a combination of either bone dust, bone wax and/or fibrin sealant. Preservation of serviceable hearing was possible in at least 58% of patients across published studies [ 10 12 ]. It is encouraging that even if complete exposure of the labyrinthine segment is required via a transcrusal approach, it may be possible to preserve sensorineural hearing.…”
Section: Discussionmentioning
confidence: 99%
“…The focal combined transpetrosal approach performed by the authors was described in detail previously. 4 It is based on: (1) small periauricular skin incision; (2) no bone flap elevation and precise drilling of the petrous (including the apex) and squamous parts of the temporal bone; (3) extensive middle fossa reverse dural peeling; (4) tentorial peeling; (5) no retractors on temporal lobe and cerebellum; and (6) minimal exposure of the brain parenchyma. The horizontal splitting of the tentorial dural layers adds further extradural access to the posterior and middle cranial fossa and protection to the temporal lobe and Labbé vein complex.…”
Section: Surgical Techniquementioning
confidence: 99%
“…However, over the years, it has been demonstrated that the violation of the labyrinthine structures, accidentally or intentionally, does not inexorably lead to hearing loss, and this has led to a re-examination of this problem by skull base surgeons. 1,2 The labyrinth obscures the view of the presigmoid space external and internal to the dura mater, which has a great impact on the visualization of deeper anatomic structures such as the abducens nerve and the basilar artery. 3 The present technical note proposes to describe a modification to the translabyrinthine approach with restricted removal of only the superior semicircular canal (SSC) during the focal combined petrosectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation